Analyzing Students’ Skills in Using Passive Voice Simple Past Tense at Second Grade of High School - Sapudra, Wawan; Syukron Sidik, Ahmad; Hendriani, Ria (Universitas Qamarul Huda Badaruddin, 2024)
This study investigates the ability of second-grade students at MA Da’watul Khaer Kumbak Luah to use the Passive Voice in the Simple Past Tense and the obstacles they face in the learning process. Employing a descriptive qualitative research design, data were gathered through observations, interviews, questionnaires, and documentation. Findings reveal that students’ mastery of the Passive Voice in Simple Past Tense is predominantly low to moderate. Students commonly struggle with distinguishing between active and passive structures, selecting appropriate forms of the verb to be, and recalling past participle (V3) forms. Internal challenges include low grammar mastery, minimal motivation, and lack of independent learning, while external factors encompass conventional teaching methods, limited media, and restricted use of technology. The study emphasizes the need for innovative, interactive teaching strategies, contextualized modules, and the integration of technology-based learning tools. These interventions are expected to enhance learners’ competence in constructing and applying Passive Voice structures accurately.